Implementasi Program Pelatihan Vokasi dan Produktivitas pada Dinas Tenaga Kerja dan Transmigrasi Provinsi Jambi - Arya Mahendra (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
The purpose of this study was to identify the implementation of the Vocational Training and Productivity Program and to identify factors influencing its implementation at the Jambi Provincial Manpower and Transmigration Office. This study used qualitative methods with data collection techniques including observation, interviews, and documentation. Based on the results, the implementation of the Vocational Training and Productivity Program in Jambi Province is not optimal, with two Van Meter and Van Horn indicators not being fully met. These include resource and budget limitations leading to reduced practice intensity, limited and outdated equipment, an unbalanced trainer ratio, and a lack of post-training mentoring. In terms of communication between implementers, although internal coordination was effective, communication with participants relied solely on a single channel (WhatsApp), and evaluations were conducted only once a year, resulting in inadequate feedback. This resulted in the program being effective only for basic training, but failing to create a sustainable impact on participants.